Nickel confined in 2D earth-abundant oxide layers for highly efficient and durable oxygen evolution catalysts. Issue 26 (29th June 2020) - Pu, Yayun; Lawrence, Matthew J.; Celorrio, Veronica; Wang, Qi; Gu, Meng; Sun, Zongzhao; Jácome, Leonardo Agudo; Russell, Andrea E.; Huang, Limin; Rodriguez, Paramaconi
Abstract : Low cost, high-efficiency catalysts towards water splitting are urgently required to fulfil the increasing demand for energy. Abstract : Low cost, high-efficiency catalysts towards water splitting are urgently required to fulfil the increasing demand for energy. In this work, low-loading (<20 wt%) Ni-confined in layered metal oxide anode catalysts (birnessite and lepidocrocite titanate) have been synthesized by facile ion exchange methodology and subjected to systematic electrochemical studies. It was found that Ni-intercalated on K-rich birnessite (Ni-KMO) presents an onset overpotential ( η onset ) as low as 100 mV and overpotential at 10 mA cm −2 ( η 10 ) of 206 mV in pH = 14 electrolyte. By combining electrochemical methods and X-ray absorption and emission spectroscopies (XAS and XES), we demonstrate Ni sites are the active sites for OER catalysis and that the Mn 3+ sites facilitate Ni intercalation during the ion-exchange process, but display no observable contribution towards OER activity. The effect of the pH and the nature of the supporting electrolyte on the electrochemical performance was also evaluated.